Capacity-building in clinical skills of rehabilitation workforce in low- and middle-income countries - Fary Khan; Bhasker Amatya; Wouter de Groote; Mayowa Owolabi; Ilyas M. Syed; Abderrazak Hajjoui; Muhammad N. Babur; Tahir M. Sayed; Yvonne Frizzell; Amaramalar S. Naicker; Maryam Fourtassi; Alaeldin Elmalik; et al. (Medical Journals Sweden, 2018)
Objective: Despite the prevalence of disability in low-and middle-income countries, the clinical skills of the rehabilitation workforce are not well described. We report health professionals' perspectives on clinical skills in austere settings and identify context-specific gaps in workforce capacity. Methods: A cross-sectional pilot survey (Pakistan, Morocco, Nigeria, Malaysia) of health professionals' working in rehabilitation in hospital and community settings. A situational-analysis survey captured assessment of clinical skills required in various rehabilitation settings. Responses were coded in a line-by-line process, and linked to categories in domains of the International Classification of Functioning, Disability and Health (ICF). Results: Respondents (n = 532) from Pakistan 248, Nigeria 159, Morocco 93 and Malaysia 32 included the following: physiotherapists (52.8%), nurses (8.8%), speech (5.3%) and occupational therapists (8.5%), rehabilitation physicians (3.8%), other doctors (5.5%) and prosthetist/orthotists (1.5%). The 10 commonly used clinical skills reported were prescription of: physical activity, medications, transfer-techniques, daily-living activities, patient/carer education, diagnosis/screening, behaviour/cognitive interventions, comprehensive patient-care, referrals, assessments and collaboration. There was significant overlap in skills listed irrespective of profession. Most responses linked with ICF categories in activities/participation and personal factors. Conclusion: The core skills identified reflect general rehabilitation practice and a task-shifting approach, to address shortages of health workers in low-and middle-income countries.